Deixis types found in Islamic songs by Maher Zain - Nuraini, Eka Indah; Karimah, Rihlatul; Virgiyanti, Diska Fatima; Fachriza, Aries; Dipta, Dinar (Universitas Islam Malang, 2024)
These days, music has a huge impact on its listeners who come from a wide range of backgrounds. Sadly, very view listeners are aware of the hidden and implicit meanings contained in the song lyrics. Thus, investigating deixis found in Islamic music by Maher Zain is crucial to provide the listeners with precise interpretations. This current study attempts to discover the varieties of deixis found in lyrics of the songs by Maher Zain (